Strengthening Economic Resilience Following the COVID-19 Crisis (Organization for Economic Cooperation & Development, 2021)
The crisis triggered by the COVID-19 pandemic has been unlike any other the world has experienced, requiring social distancing and restrictions on mobility, and rendering some economic activity impossible. This publication explores and compares the characteristics that have affected the ability of firms, workers and consumers to maintain production, employment and consumption during the COVID-19 crisis, across industries and countries.